Manajemen Berbasis Sekolah (MBS) dalam Meningkatkan Sarana Prasarana Studi Deskriftip Peran Kepala Sekolah dalam MBS di SDN 36/Rantau Panjang III - Muhammad; Megawati (Indonesian Journal Publisher, 2024)
With the aim of improving the quality of education, School-Based Management (SBM) is an educational management approach that aims to improve the quality of education by encouraging schools to have autonomy or independence and encouraging citizen participation in the decision-making process. By implementing School Based Management, schools are expected to be able to achieve educational standards and achieve quite good results. Management of school facilities and infrastructure aims to ensure that students feel what they need while at school. This study aims to determine the extent to which the existing facility infrastructure has been improved by implementing school-based management (SBM) at SDN 36/Rantau Panjang III. A qualitative descriptive study design was employed in this investigation, and the principal was interviewed and data was gathered through observation. The results of the research data show that the role of the principal in SBM in an effort to improve infrastructure facilities at SDN 36/VI Rantau Panjang III has been organized and managed quite well and is in accordance with the basic needs of the school, especially in fulfilling the standards of infrastructure facilities.